Tehri Dam: An Engineering Marvel - Adhikari, Basistha Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
Despite repeated controversy over implementing high dams in the Himalayan region, the Government of India has completed the fi rst stage of Tehri Dam hydroelectric project with power generating capacity of 1,000 MW. Being the third dam of its kind after Bhakra and Pong in India, Tehri Dam has faced several social, legal and engineering challenges. Most of them may be lessons for the whole Himalayan region including Nepal. The Tehri Dam Project was initiated in 1970s with technical support from the USSR. Later, with the establishment of Tehri Hydro Development Corporation, the project was resumed with new dimensions to be developed in three stages: Tehri Dam Project with 1,000 MW in Stage 1, Koteshwar Power Plant with 400 MW capacity in Stage-2, and Tehri Pump Storage Plant with 1,000 MW capacity providing altogether 2,400 MW of clean hydro electric energy in Stage-3. The fi rst stage project was commissioned in 2006 while the second stage is under construction. The major outcome of the Tehri Dam Project is its successful implementation of rehabilitation and resettlement plans through the establishment of the New Tehri town in the Garhwal hills and adjacent areas. This article shares the technical innovation of Tehri Dam Project from socio-engineering perspective. Key words : Tehri Dam Project; Storage hydropower project; Rehabilitation and resettlement; India DOI: 10.3126/hn.v5i0.2481 Hydro Nepal Vol. 5, July 2009 Page:26-30